EFFECTIVE COMMUNICATION FOR SPECIAL NEEDS CHILDREN EDUCATORS - Ucik Ana Fardila (JARES (Journal of Academic Research and Sciences), 2018)
Effective communication is very important for learning process in the class. Effective communication from teacher to parent especially has important role to reach learning achievement for children with special needs ’s classes. The key of well delivered communication is when communicator and communicant have the same message in a same perception thus will have a same understanding without meaning decreasion. Information could be delivered precisely and accurately if teacher and parent have a same understanding of the message. Communication system is necessary in children with special needs school system as the main tool of academic achievement evolvement, psychological achievement, and for student physical and mental development. Two way communication between teacher and parent become the main role of quality of children with special needs family. Communication from parent could help teacher have better knowledge about student that would help teacher to plan their class in the best method they could teach to be effective learning for each student. for children with special needs class could not only involve teacher and school system but also a good network system from parent and institutions from outside class that has impact in the children with special needs physical and mental development. It is necessary to have a certain system to connect every role in children with special needs environment to record their development through communication network system involving school, family, health institution and community as communication ’s instrument support so the learning achievement would be optimally performed